Bottom‐Up Synthesized MoS2 Interfacing Polymer Carbon Nanodots with Electrocatalytic Activity for Hydrogen Evolution. Issue 29 (31st March 2020) - Kagkoura, Antonia; Canton‐Vitoria, Ruben; Vallan, Lorenzo; Hernandez‐Ferrer, Javier; Benito, Ana M.; Maser, Wolfgang K.; Arenal, Raul; Tagmatarchis, Nikos
Abstract: The preparation of an MoS2 –polymer carbon nanodot (MoS2 ‐PCND) hybrid material was accomplished by employing an easy and fast bottom‐up synthetic approach. Specifically, MoS2 ‐PCND was realized by the thermal decomposition of ammonium tetrathiomolybdate and the in situ complexation of Mo with carboxylic acid units present on the surface of PCNDs. The newly prepared hybrid material was comprehensively characterized by spectroscopy, thermal means, and electron microscopy. The electrocatalytic activity of MoS2 ‐PCND was examined in the hydrogen evolution reaction (HER) and compared with that of the corresponding hybrid material prepared by a top‐down approach, namely MoS2 ‐PCND(exf‐fun), in which MoS2 was firstly exfoliated and then covalently functionalized with PCNDs. The MoS2 ‐PCND hybrid material showed superior electrocatalytic activity toward the HER with low Tafel slope, excellent electrocatalytic stability, and an onset potential of −0.16 V versus RHE. The superior catalytic performance of MoS2 ‐PCND was rationalized by considering the catalytically active sites of MoS2, the effective charge/energy‐transfer phenomena from PCNDs to MoS2, and the synergetic effect between MoS2 and PCNDs in the hybrid material. Abstract : Facile and fast : A facile and fast bottom‐up approach involving thermal decomposition of ammonium tetrathiomolybdate and the in situ complexation of Mo with carboxyl groups on the surface of polymer carbon nanodots (PCNDs) was used to prepare a hybrid material consisting of MoS2 and PCNDs. The thus‐obtained MoS2 ‐PCND electrocatalyst showed superior activity towards the hydrogen evolution reaction and outperformed the corresponding material acquired by a top‐down approach.